Taxonomy of the Afrotropical genus Leptomenes Giordani Soika, with description of a new species from South Africa (Hymenoptera: Vespidae: Eumeninae) - Selis, Marco (Zootaxa, 2023)
A new South African species of Leptomenes Giordani Soika, 1939, namely Leptomenes obliquepunctatus Selis, sp. nov., is described. The Malagasy genus Malgachemenes Gusenleitner, 1992 is synonymized with Leptomenes syn. nov. (Leptomenes angustus comb. nov.). Leptomenes extremus Gusenleitner, 2005 is a junior synonym of Raphiglossa lemuriae Giordani Soika, 1941 syn. nov. The previously published key for the continental species is updated.